High-resolution optical coherence tomography of subpigment epithelial structures in patients with pigment epithelium detachment secondary to age-related macular degeneration. Issue 8 (13th June 2012) - Clemens, Christoph R; Krohne, Tim U; Charbel Issa, Peter; Helb, Hans-Martin; Kosanetzky, Nina; Lommatzsch, Albrecht; Holz, Frank G; Eter, Nicole
Abstract : Background: The pathophysiology of pigment epithelial detachment (PED) secondary to age-related macular degeneration (AMD) is as yet incompletely understood and treatment remains challenging. Spectral domain optical coherence tomography (SD-OCT) allows for improved morphological characterisation of the space underneath the retinal pigment epithelium (RPE). Objective: To investigate eyes with PED for structures underneath the detached RPE cell layer. Methods: In a retrospective observational case study, SD-OCT scans of AMD-related PEDs were assessed for the presence of distinctive morphological features in the space between the detached RPE and inner Bruch's membrane. Results: Structures present in the space between the detached RPE and Bruch's membrane were found in 14 of 90 eyes with AMD-related PED. Each of these eyes shows hyper-reflective material underneath the PED, presenting as highly reflective, multilayered, laminar structures, usually orientated parallel to Bruch's membrane. Conclusions: The findings indicate that SD-OCT may be useful for a more refined phenotypic stratification of AMD-associated PED. Further studies are warranted to explore the correlates on other imaging modalities, to investigate the composition of this material and to assess the potential prognostic relevance of this new finding.